Ki or Psi, Anomalous Remote Effects of Mind-Body System: Biophysical Approach to Unknown Power by Hideyuki Kokubo - Bobrow, Robert (Journal of Scientific Exploration, 2019)
This is an interesting book. It examines healing bio-energy (“Qi” in China, “Ki” in Japan) phenomena and measurement techniques. The author, Hideyuki Kokubo, is a biophysicist and director of the International Research Institute Chiba, Japan and his take on the subject is analytical and scientific. Much of the book details the use of an ordinary cucumber as a bio-energy detector. There are original experiments and full descriptions of methods. Essentially, cucumber slices can be used as bio-sensors: In the presence of a human energy field they form biophotons, fluoresce differently and emit a vapor, all of which are measurable. An introductory chapter explains the concept of Ki, historically and in modern Japan. It includes some history of the cucumber, agriculturally and in healing (in a Buddhist ritual known as kyuuri-kaji). The closing chapter recounts Japanese studies on anomalous phenomena during the last 50 years. It discusses the impact of Uri Geller’s visit to Japan in 1974 and the impact of Chinese studies, particularly the qigong boom in Japan during the 1980s, shortly after its introduction there. Referenced also are studies of non-contact healing, reincarnation, clairvoyance, ESP, and anomalous incidents in hospitals. There is a section on toh-ate, a Japanese martial art through which a non-contact attack is made. This is a short, well-organized book, and the overriding theme is that some psi effects can be measured objectively, scientifically, and quantifiably. The last sentence of the author’s final remarks sums it: “If something exists actually, it can be examined by experiments.” The last acknowledgement is to cucumbers and their farmers. I know I’ll never look at a cucumber the same way.